Respuesta :
[tex]36^{- \frac{1}{2} }= \cfrac{1}{36^{ \frac{1}{2} }} = \cfrac{1}{(6^2)^{ \frac{1}{2} }} = \cfrac{1}{6} [/tex]
ANSWER
[tex]( {36})^{ (- \frac{1}{2}) } = \frac{1}{6} [/tex]
EXPLANATION
The given expression is
[tex] {36}^{( - \frac{1}{2} )} [/tex]
This is having a negative index. We must first of all change to a positive index.
Recall that,
[tex] {a}^{ - m} = \frac{1}{ {a}^{m} } [/tex]
We apply this law of exponents to get,
[tex] {36}^{( - \frac{1}{2} )} = \frac{1}{ {36}^{( \frac{1}{2} )} } [/tex]
We cab rewrite the given expression to obtain;
[tex] {36}^{( - \frac{1}{2} )} = \frac{1}{ \sqrt{36} } [/tex]
This will simplify to give us,
[tex] {36}^{( - \frac{1}{2} )} = \frac{1}{ 6 } [/tex]
[tex]( {36})^{ (- \frac{1}{2}) } = \frac{1}{6} [/tex]
EXPLANATION
The given expression is
[tex] {36}^{( - \frac{1}{2} )} [/tex]
This is having a negative index. We must first of all change to a positive index.
Recall that,
[tex] {a}^{ - m} = \frac{1}{ {a}^{m} } [/tex]
We apply this law of exponents to get,
[tex] {36}^{( - \frac{1}{2} )} = \frac{1}{ {36}^{( \frac{1}{2} )} } [/tex]
We cab rewrite the given expression to obtain;
[tex] {36}^{( - \frac{1}{2} )} = \frac{1}{ \sqrt{36} } [/tex]
This will simplify to give us,
[tex] {36}^{( - \frac{1}{2} )} = \frac{1}{ 6 } [/tex]